CACNA1A Mutations Associated With Epilepsies and Their Molecular Sub-Regional Implications - Li, Xue-Lian; Li, Zong-Jun; Liang, Xiao-Yu; Liu, De-Tian; Jiang, Mi; Gao, Liang-Di; Li, Huan; Tang, Xue-Qing; Shi, Yi-Wu; Li, Bing-Mei; He, Na; Li, Bin; et al. (Frontiers in Molecular Neuroscience, 2022)
Purpose: Previously, mutations in the calcium voltage-gated channel subunit alpha1 A (CACNA1A) gene have been reported to be associated with paroxysmal disorders, typically as episodic ataxia type 2. To determine the relationship between CACNA1A and epilepsies and the role of molecular sub-regional on the phenotypic heterogeneity. Methods: Trio-based whole-exome sequencing was performed in 318 cases with partial epilepsy and 150 cases with generalized epilepsy. We then reviewed all previously reported CACNA1A mutations and analyzed the genotype-phenotype correlations with molecular sub-regional implications. Results: We identified twelve CACNA1A mutations in ten unrelated cases of epilepsy, including four de novo null mutations (c.2963_2964insG/p.Gly989Argfs*78, c.3089+1G>A, c.4755+1G>T, and c.6340-1G>A), four de novo missense mutations (c.203G>T/p.Arg68Leu, c.3965G>A/p.Gly1322Glu, c.5032C>T/p.Arg1678Cys, and c.5393C>T/p.Ser1798Leu), and two pairs of compound heterozygous missense mutations (c.4891A>G/p.Ile1631Val& c.5978C>T/p.Pro1993Leu and c.3233C>T/p.Ser1078Leu&c.6061G>A/p.Glu2021Lys). The eight de novo mutations were evaluated as pathogenic or likely pathogenic mutations according to the criteria of American College of Medical Genetics and Genomics (ACMG). The frequencies of the compound heterozygous CACNA1A mutations identified in this cohort were significantly higher than that in the controls of East Asian and all populations (P=7.30×10-4, P=2.53×10-4). All of the ten cases were ultimately seizure-free after antiepileptic treatment, although frequent epileptic seizures were observed in four cases. Further analysis revealed that EA2 had a tendency of higher frequency of null mutations than epilepsies. The missense mutations in severe epileptic phenotypes were more frequently located in the pore region than those in milder epileptic phenotypes (P=1.67×10-4); de novo mutations in the epilepsy with intellectual disability (ID) had a higher percentage than those in the epilepsy without ID (P=1.92×10-3). Conclusion: This study suggested that CACNA1A mutations were potentially associated with pure epilepsy and generated a spectrum of epileptic phenotypes ranging from the mild form of epilepsies such as absence epilepsy or partial epilepsy, to the severe form of developmental epileptic encephalopathy. The clinical phenotypes variability is potentially associated with the molecular sub-regional of the mutations.